IMPLEMENTATION OF E-GOVERNMENT IN POPULATION ADMINISTRATION AND LICENSING SERVICES IN REMOTE AREAS: AN EVALUATION OF SUCCESSES AND CONSTRAINTS - Regina Argianti; Dede Sri Kartini (Program Studi Administrasi Negara Universitas Serang Raya, 2025)
The implementation of e-government has become a global trend to enhance the efficiency, transparency, and accessibility of public services. In Indonesia, e-government is governed by the Sistem Pemerintahan Berbasis Elektronik (SPBE), emphasizing the digital transformation of public services, including population administration and licensing. This study aims to evaluate the success and challenges of e-government implementation in remote areas, focusing on the infrastructure, human resource capacity, and public adoption. The research utilizes a systematic literature review (SLR) methodology to synthesize findings from relevant studies over the past decade. The results indicate that while e-government has improved efficiency and transparency in many regions, significant challenges persist, such as limited infrastructure, low digital literacy, and insufficient training for public officials. These findings emphasize the need for comprehensive strategies to address these challenges, including strengthening digital literacy, equitable infrastructure development, and increasing public awareness of e-government benefits. This study provides a framework for improving the effectiveness and inclusivity of e-government in remote areas of Indonesia.